Writing the Trenches: What Students of Technical Writing and Literature Can Learn Together - Baake, Ken; Shelton, Jen (Journal of technical writing and communication, 2017)
We argue for a course in which students analyze writing about a common topic—in this case World War I—from multiple genres (e.g., poetry and technical manuals). We address the divide between instruction in pragmatic and literary writing and calls to bridge that gap. Students working in disparate areas of English learn the strengths and the limitations of their fields, and how text represents and promotes different interpretations of reality. Such written representations do not neatly line up along a utilitarian-literary binary but are more closely interwoven in the presence of a profound subject such as war.